2011
DOI: 10.1177/107327481101800206
|View full text |Cite
|
Sign up to set email alerts
|

Management of Isolated Adrenal Lesions in Cancer Patients

Abstract: Background: Adrenal lesions are commonly identifi ed in patients with extra-adrenal cancer. When lesions are present, it is important to identify if the lesion is a metastasis of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 78 publications
4
23
1
Order By: Relevance
“…Our study found that approximately 40% of patients with primary cancer did not have a malignant adrenal lesion, similar to previous reports [26]. Moreover, adrenal lesions in patients without primary cancer were all benign or owing to hyperplasia, consistent with the low frequency (approximately 10%) of primary adrenal tumours [26]. Of the patients without known primary cancer, 8.4% had an unenhanced attenuation of .10 HU and 3.1% had an SUV max ratio of .2.5.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our study found that approximately 40% of patients with primary cancer did not have a malignant adrenal lesion, similar to previous reports [26]. Moreover, adrenal lesions in patients without primary cancer were all benign or owing to hyperplasia, consistent with the low frequency (approximately 10%) of primary adrenal tumours [26]. Of the patients without known primary cancer, 8.4% had an unenhanced attenuation of .10 HU and 3.1% had an SUV max ratio of .2.5.…”
Section: Discussionsupporting
confidence: 81%
“…Our study found that PET/CT was efficient in differentiating between benign and malignant adrenal lesions. Our study found that approximately 40% of patients with primary cancer did not have a malignant adrenal lesion, similar to previous reports [26]. Moreover, adrenal lesions in patients without primary cancer were all benign or owing to hyperplasia, consistent with the low frequency (approximately 10%) of primary adrenal tumours [26].…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies indicate that a history of malignancy increases the likelihood of an adrenal lesion being malignant [4,21]. In the present study, previous malignancy was found to be associated with an increased risk of malignancy in univariate analysis, but not in multivariate logistic regression.…”
Section: Discussioncontrasting
confidence: 65%
“…adrenocortical carcinoma, pheochromocytoma) because it is rarely informative and potentially hazardous. 16 In this setting is preferred to biopsy other lesion which involves the same stage disease. If the adrenal mass is the lesion with the highest stage disease, it is mandatory to perform an appropriate workup prior to performing an EUS-FNA to rule out primary adrenal tumors.…”
Section: Prioritizing Lesions Samplingmentioning
confidence: 99%